Implikasi Tradisi Mappasiewa Ada’ terhadap Harmonisasi Rumah Tangga dalam Perkawinan Masyarakat Bugis di Segeri Kabupaten Pangkajene dan Kepulauan - Hasliyawatih T.; Basri, Rusdaya; Rahmawati; Sudirman L.; Muchsin, Agus (Al-Mizan (e-Journal), 2024)
Harmony is something that is expected by a married couple in their marriage. This article describes the implications of the mappasiewa ada' tradition on household harmonisation in Bugis marriages in Segeri, Pangkajene and Islands Regency using descriptive qualitative research with a philosophical and normative approach and analysed with ’urf  (tradition theory) and maslahah (kindness theory). The results showed that the practice of mappasiewa ada' tradition in Bugis community marriage is still preserved as a tradition in marriage which has philosophical meaning with symbols. This tradition has a kindness (maslahah) impact and a badness (mafsadah) impact for the bride and groom in building household harmony. The mappasiewa ada' tradition is in accordance with Islamic teachings in the form of good tradition (’urf shahih) which can be preserved as long as it does not deviate from the objectives of sharia or maqashid ash-shari'ah (the purpose of Islamic law), namely: preservation of offspring (muhafadzah al-nasl). It can also be understood as optimism (tafa'ul), because every symbol in the tradition contains a hope or prayer symbolised by an object. If the mappasiewa ada' tradition is not understood comprehensively, people may consider it a practice that contains polytheism (syirik). However, if an Islamic and cultural approach is used, then cultural Islamisation can be carried out, so that the mappasiewa ada' tradition can be preserved and become an important part of the Bugis marriage tradition.